Blue Ocean Health Care bridging people to an affordable health care system - Miranda, Maria Teresa S.; Concepcion, Sylvia B.; Soledad, Miguel D. (Davao City School of Management, University of the Philippines Mindanao, 2006)
Blue Ocean Health Care (BOHC), a business unit of the Pontevera Group of Companies, was established in 2001 to serve the health care needs of the fishing conglomerate. Compared with pre-need companies where a substantial amount of capital is needed to start business operations, BOHC is different in this aspect because it commenced its undertaking without any cash outlay from its owners. Instead, it was able to fully operate and survive by making use of the initial collection of premiums from member-companies as a start up fund and utilizing the resources and facilities provided from its mother company. While it is operating primarily for the employees and dependents of PG, the firm aims to expand eventually and cater to the outside market. Consistent with the thrust to sustain its growth momentum, the company is now embarking on programs to further professionalize its ways of doing things. One such initiative is the installation of a formal strategic planning mechanism. Moreover, the lack of focused attention over the firm's activities has been noted to result in the management's failure to regularly monitor the company's general performance. Consequently, BOHC was unable to pre-empt the apparent weakening of its financial positions caused by higher utilization levels in the succeeding two years of its inception. In an attempt to guide the firm's future directions, this paper intends to answer this corporate need. It presents a strategic plan developed for BOHC to serve as a guiding force, not only for the firm's management, but also for the administrator and staff who run its day-to-day operations. The plan was made following the context of the strategic management framework of Pearce and Robinson. An analysis of the company's external conditions was carried out by looking at the prevailing scenario in the industry where it belongs. The political, economic, socio-cultural, and technological factors affecting its overall performance were evaluated and the business as an organization was dissected in terms of its operations, financial performance, and Human Resources. The analysis indicated that the company has significant internal inadequacies as its strengths are deemed insufficient to overcome its weaknesses. However, BOHC demonstrates considerable potential to exploit available opportunities and allay the threats that exit in its peripheral environment. Several strategic options were formulated through the use of quantitative tools and among the generated alternatives, product development and market penetration present the best opportunities for BOHC as they allow the firm to cope with its internal deficiencies and respond adequately to external conditions. Long-term objectives, implementing programs and the control mechanisms need were mapped out to ensure effective execution of the strategic choice and steer BOHC towards a challenging future.
Thesis, Graduate (Master in Management)--University of the Philippines Mindanao, April 2006.
Keywords: Strategic plan